Treatment of isolated fourth metacarpal neck fractures using the closed reduction and percutaneous intermetacarpal and external fixation - Fan, Anwei; Zhang, Xiao; Zhang, Xu; Zhang, Lu; Peng, Aqin; Yu, Xuanrong (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2023)
The isolated fourth metacarpal neck fracture is uncommon, and the appropriate management is still debatable. The aim of this retrospective study was to introduce a closed reduction and percutaneously intermetacarpal K-wire fixation external technique to treat the isolated fourth metacarpal neck fracture. From October 2013 to January 2018, 21 patients with closed-isolated fourth metacarpal neck fractures (angulation ≥35°, rotation ≥5°, or shortening ≥5 mm) were treated with the closed reduction and percutaneous intermetacarpal and external fixation technique. Total active motion, grip strength of the hand, dorsal prominence, and patient satisfaction were assessed. Follow-up lasted 28 months (range, 24–37 months). All patients obtained bone healing at a mean time of 5 weeks (range, 4–8 weeks). External fixation devices were removed when bone healing achieved. The mean total active motion reached 97.5% (range, 92.9%–100%) of opposite side. There were 18 excellent and 3 good results. The mean grip strength reached 98.4% (range, 96.2%–100%) of the opposite hands. Based on the 100-mm visual analogue scale, the mean dorsal prominence was 0 (range, 0 to 1). Based on the Short Assessment of Patient Satisfaction, the mean satisfaction score was 26 (range, 24 to 28). The closed reduction and percutaneous intermetacarpal and external fixation technique is useful and reliable for treating the isolated fourth metacarpal neck fracture. The technique can effectively restore the fracture deformities and maintain the reduction stably, resulting in good hand function. Therapeutic study, Level IV.